LANDSCAPE EVALUATION OF VISUAL ATTRACTIVENESS TO IMPROVE URBAN LIVING AT NAVA PARK - Purniawan, Agus; Simangunsong, Nur Intan; Fitri, Rini; Fauzi, Reza (Journal of Synergy Landscape, 2022)
The Botanic Park at Nava Park has an area of ​​10 hectares, consisting of green areas and open spaces for recreation and various uses, including 3.5 hectares of the artificial lake and a 15 km jogging track. However, a lack of green planning affects its attractiveness to visitors of the Botanic Park, and its existing visual potential has not been optimally utilized. This is apparent from the inexistence of outdoor activities facilities that could take advantage of this potential. The study aims to identify visual potential as the basis for developing the landscape of the Botanic Park. This study used a qualitative method with observation as the research instrument and a potential visual assessment using the Visual Resource Assessment Procedure (VRAP) and Master Plan Evaluation. Data analysis used interval classes, classified according to their visual qualities. The research findings were the visual quality of the landscape, classified into three zones of high, medium, and low visual qualities, which would help place facilities in further landscape development. The best macro visual qualities were found in the Meandering River Zone, with a score of 17, followed by the Serenity Lake Zone, with a score of 15. The lowest was in the Green Land/Wet Land Zone, with a score of 14. This study provided recommendations for managing the Botanic Park at Nava Park Bumi Serpong Damai (BSD) in the form of a green landscape design as a visual attraction.